Deep bite treatment (Research, Society and Development, 2022)
The deep bite, or exaggerated overbite, is a malocclusion that presents a multifactorial etiology, which requires a precise diagnosis to obtain a correct treatment plan, aiming a good aesthetic and functional result. Therefore, it is a problem that we often encounter with orthodontic treatments. A Class II, Division 2 malocclusion is characterized by retracted upper teeth (inclined toward the roof of the mouth) and an increased overbite (deep overbite), which can cause oral problems and affect appearance. This problem can be corrected by using special dental appliances (functional appliances) that move the front teeth forward and change the growth of the upper or lower jaws, or both. Most functional appliance appliances are removable and this treatment approach generally does not require the extraction of any permanent teeth. Additional treatment with fixed appliances may be necessary to ensure the best result. The mechanics of treatment for deep bite correction will depend on its etiology, expected growth and vertical dimension. The deep bite treatment approach can follow three lines, the intrusion of anterior teeth, the extrusion of posterior teeth or the association of the two techniques. Through a literature review the present study aimed to highlight the importance of early treatment of this malocclusion, avoiding future damage to the stomatognathic system, also increasing the success and stability after treatment.